2010
DOI: 10.1152/jn.00971.2009
|View full text |Cite
|
Sign up to set email alerts
|

Properties of GABAergic Neurons in the Rostral Solitary Tract Nucleus in Mice

Abstract: The rostral nucleus of the solitary tract (rNST) plays a pivotal role in taste processing. The rNST contains projection neurons and interneurons that differ in morphology and intrinsic membrane properties. Although characteristics of the projection neurons have been detailed, similar information is lacking on the interneurons. We determined the intrinsic properties of the rNST GABAergic interneurons using a transgenic mouse model that expresses enhanced green fluorescent protein under the control of a GAD67 pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 74 publications
3
27
1
Order By: Relevance
“…Thus it would appear that this mouse is a more effective model for comparing properties of GABAergic with non-GABAergic neurons than some other commercially available strains. For example, the "GIN" mouse expresses EGFP mainly in somatostatin GABAergic neurons in the neocortex (Oliva et al 2000), and in the rNST EGFP expression is confined to just half of the GABAergic cells (Wang and Bradley 2010a) and is particularly abundant in the ventral subnucleus (Travers et al 2007;Wang and Bradley 2010a). This preferential distribution contrasts sharply with the homogeneous pattern observed in the GAD67-EGFP knockin mouse in the present investigation (Fig.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Thus it would appear that this mouse is a more effective model for comparing properties of GABAergic with non-GABAergic neurons than some other commercially available strains. For example, the "GIN" mouse expresses EGFP mainly in somatostatin GABAergic neurons in the neocortex (Oliva et al 2000), and in the rNST EGFP expression is confined to just half of the GABAergic cells (Wang and Bradley 2010a) and is particularly abundant in the ventral subnucleus (Travers et al 2007;Wang and Bradley 2010a). This preferential distribution contrasts sharply with the homogeneous pattern observed in the GAD67-EGFP knockin mouse in the present investigation (Fig.…”
Section: Discussioncontrasting
confidence: 70%
“…We used a transgenic mouse expressing EGFP under the control of the endogenous promoter for GAD67, a synthetic enzyme for GABA. In contrast to the commercially available "GIN" mouse, which only expresses GFP in a particular subset of rNST GABAergic neurons (Travers et al 2007;Wang and Bradley 2010a), this GAD67-GFP knockin strain has been shown to produce EGFP in virtually all cells expressing GAD67 (Brown et al 2008;Kaneko et al 2008;Ono et al 2005;Tamamaki et al 2003), allowing for a more complete identification of GABAergic neurons in the NTS. Because of reports that monosynaptic inputs to GABAergic neurons in the rNST may diminish during development in rat (Wang et al 2012) but evidence for presynaptic inhibition of monosynaptic vagal inputs to cNST GABAergic neurons in mature as well as young mice (Glatzer et al 2007), we included both mouse pups (P14 -18) and adult mice (6 -11 wk) in our study.…”
Section: Methodsmentioning
confidence: 99%
“…2D). Thus, all Gaa −/− tissues demonstrated robustly positive staining for CC3 in a region that included the medial NTS and cuneate nucleus (Ganchrow et al, 2014; Tokita et al, 2009; Wang and Bradley, 2010; Zaidi et al, 2008). The Tunel stain showed a similar pattern with positive staining in an area that extended from the area postrema through the NTS (Fig.…”
Section: Resultsmentioning
confidence: 93%
“…It seems likely that MOR ligands could modulate GABA release in the rNST/RF as well. GABA neurons and enkephalin/endomorphin fibers are densely distributed in the rNST and RF and have overlapping distributions (44,48,56,65,70). Moreover, a recent electron microscopic study suggested that some enkephalin terminals may actually synapse onto GABAergic neurons in the rNST (28).…”
Section: Discussionmentioning
confidence: 99%